Dietary Supplementation With Citrus Extract Altered the Intestinal Microbiota and Microbial Metabolite Profiles and Enhanced the Mucosal Immune Homeostasis in Yellow-Feathered Broilers - Yu, Miao; Li, Zhenming; Chen, Weidong; Wang, Gang; Cui, Yiyan; Ma, Xianyong (Frontiers in Microbiology, 2019)
The present study aimed to investigate the effect of citrus extract (CE) on intestinal microbiota, microbial metabolite profiles, and the mucosal immune status in broilers. A total of 540 1-d-old yellow-feathered broilers were randomly allotted into 3 groups and either fed a basal diet (control group), or a basal diet containing 10 mg/kg zinc bacitracin (antibiotic group), 10 mg/kg CE (CE group), respectively. Each treatment consisted of 6 replicates, with 30 broilers per replicates. After 63-d feeding, 2 broilers per replicate were randomly selected and slaughtered, the ileal and cecal digesta and ileal tissue were collected for microbial composition, microbial metabolites, and genes expression analysis. The results showed that CE significantly increased the abundance of Barnesiella and Blautia compared with antibiotic group (adjusted P < 0.05), while decreased the abundance of Alistipes and Bacteroides (adjusted P < 0.05). Meanwhile, CE also increased the numbers of Bifidobacterium and Lactobacillus compared with control and antibiotic groups (P < 0.05), while decreased the number of Escherichia coli (P < 0.05). For microbial metabolites, dietary supplementation with CE increased the concentrations of lactate, total short-chain fatty acids, acetate, and butyrate in the cecum compared with control and antibiotic groups (P < 0.05), while decreased the concentrations of amino acid fermentation products (ammonia, amines, p-cresol, and indole) (P < 0.05). Additionally, supplementation with CE up-regulated (P < 0.05) the mRNA expression of intestinal barrier genes (ZO-1 and Claudin) in the ileum compared with both control and antibiotics groups. However, antibiotic treatment induced gut microbiota dysbiosis, altered the microbial metabolism, and disturbed the innate immune homeostasis. In summary, these results provide evidence that dietary supplementation with CE can improve the intestinal barrier function by changing microbial composition and metabolites, likely toward a host-friendly gut environment. This suggests that CE may possibly act as an efficient antibiotic alternative for yellow-feathered broilers production.